Processing and characterization of high environmental efficiency composites based on PLA and hazelnut shell flour (HSF) with biobased plasticizers derived from epoxidized linseed oil (ELO). (1st February 2016) - Balart, J.F.; Fombuena, V.; Fenollar, O.; Boronat, T.; Sánchez-Nacher, L.
Abstract: Different amounts of epoxidized linseed oil (ELO) have been added to poly(lactic acid)-PLA composites with hazelnut shell flour (HSF) to provide a plasticizing effect and improve the low intrinsic ductile properties of PLA/HSF composites. Mechanical, thermal, thermo-mechanical and dynamic mechanical properties have been studied in terms of the weight percentage ELO. Mechanical resistant properties in both tensile and flexural tests decrease with wt.% ELO while a remarkable increase with wt.% ELO is obtained. These results reveal a clear plasticization effect of ELO but, in addition, internal structure of PLA/HSF/ELO composites shows good PLA-HSF (matrix-particle) interactions so that indicating that ELO also provides a coupling effect between PLA matrix and HSF filler. ELO addition leads to a decrease in storage modulus (G′) obtained by dynamic mechanical thermal analysis (DMTA) in torsion mode thus giving clear evidence of the plasticization effect of ELO. Overall, the use of ELO in PLA/HSF composites is an attracting way to improve the low intrinsic fragility of these green composites; furthermore, ELO provides an improvement on thermal stability and a coupling effect between the polymer matrix and the surrounding lignocellulosic filler.